Understanding the replication biology of Providence virus: elucidating the function of non-structural proteins - Nakayinga, Ritah (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
Tetraviruses are non-enveloped, small insect RNA viruses with a single stranded positive RNA genome that is either monopartite or bipartite. Providence virus (PrV) is the only member of the three tetravirus families with a viral replicase similar to the replicases of tombusviruses and umbraviruses. The principle aim of this thesis was to study PrV replication, focusing on subcellular localization and potential interactions between PrV replication proteins. The first objective of this study was to generate an anti-p104 antibody that does not cross-react with p40. Expression of the C-terminal portion of p104 in E. coli resulted in no detectable protein. Further expression in an insect cell based expression system resulted in the production of an insoluble protein. Attempts to improve protein solubility with a range of solubilization treatments were unsuccessful. Bioinformatic analysis was used to detect an antigenic region at the C-terminus of p104 and the peptide was used to raise anti-p104 antibodies. These antibodies did not detect native protein by western blot detection however they were used for immunoprecipitation. The establishment of the subcellular localization of PrV required two approaches; immunofluorescence in persistently infected Helicoverpa zea MG8 cells using antip40 and anti-dsRNA antibodies and the expression of EGFP-replicase fusion protein in Spodoptera frugiperda Sf9 cells. Replication of PrV was found to take place in cytosolic punctate structures. Co-immunoprecipitation experiments revealed that p40 self-interacts and interacts with p104. Bioinformatic analysis of PrV p104 suggests that the RdRp is similar to viral RdRps of the carmo-like supergroup II. Potential RNA binding regions are present within p104. A potential p40 interaction domain that shares hydrophilic and surface exposed properties with the TBSV p33 interaction domain is present. A putative arginine-rich region and disordered C-terminal region is present in p130. In conclusion, PrV p104 is the viral replicase. The resemblance of the expression strategy and putative functional domains with tombusviruses and umbraviruses suggest that PrV replication is related to the replication system of the tombusviruses and umbraviruses. This has led to propose that tetravirus replication strategies are diverse and raises questions on the origin and evolution of PrV.
Keywords: Insects -- Viruses; Viruses -- Reproduction; Tombusviridae; RNA viruses; RNA polymerases